Development of Role Playing Based on Traffic Sign Miniature Learning Media in Elementary Schools - Suttrisno, Suttrisno; Shalihah, Fika Rachmatus; Fithriyah, Dewi Niswatul (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In an era where traffic discipline is increasingly neglected, Specific Background: instilling traffic rule awareness from an early age is critical. The Indonesian subject for grade III elementary students includes material on traffic signs. Knowledge Gap: However, conventional teaching methods relying on lectures and textbooks often lead to student disengagement, especially when interpreting symbolic traffic signs. Aims: This study aims to develop a role-playing-based miniature traffic sign learning media to enhance student comprehension and engagement. Results: Utilizing the ADDIE Research and Development model, product validation involved media, material, and language experts, as well as students. Validation results showed scores of 90% (media), 88.5% (material), and 90% (language), while student responses reached 96%, all categorized as